Etyka w pracy audytora wewnętrznego - Krawczyk, Marzena; Sekuła, Piotr (Annales. Etyka w Życiu Gospodarczym, 2008)
Internal audit provides an independent and objective opinion to the Board on risk management, control and governance, by measuring and evaluating their effectiveness in achieving an organisation’s agreed objectives. It also provides an independent and objective consultancy service to help line management improve the organisation’s processes. Internal auditors should respect in their work some ethical rules, especially these included in the Code of Ethics formed by the IIA. This code is intended to clarify the standard of conduct expected from all members of the internal audit unit. The main four principles that should be observed are as follows: integrity, objectivity, competency and confidentiality Being ethical in internal audit is necessary in order to win the trust of the environment in which auditors work. However, declaring one’s readiness to respect the Code of Ethics is not enough. Much more important is to implement and comply with given rules in carrying out audit duties.